Clinical utility of intrathoracic impedance monitoring to alert patients with an implanted device of deteriorating chronic heart failure - Vollmann, Dirk; Nägele, Herbert; Schauerte, Patrick; Wiegand, Uwe; Butter, Christian; Zanotto, Gabriele; Quesada, Aurelio; Guthmann, Axel; Hill, Michael R.S.; Lamp, Barbara (European heart journal, 2007)
Aims To evaluate the utility of intrathoracic impedance monitoring for detecting heart failure (HF) deterioration in patients with an implanted cardiac resynchronization/defibrillation device. Methods and results Patients enrolled in the European InSync Sentry Observational Study were audibly alerted by a device algorithm if a decrease in intrathoracic impedance suggested fluid accumulation. Clinical HF status and device data were assessed at enrolment, during regular follow-up, and if patients presented with an alert or HF deterioration. Data from 373 subjects were analysed. Fifty-three alert events and a total of 53 clinical events (HF deterioration defined by worsening of HF signs and symptoms) were reported during a median of 4.2 months. Adjusted for multiple events per patient, the alert detected clinical HF deterioration with 60% sensitivity (95% CI 46–73) and with a positive predictive value of 60% (95% CI 46–73). Higher NYHA class at baseline was predictive for adequate alert events during follow-up (P < 0.05). In 11 of 20 HF deteriorations without preceding alert, an upstroke of the fluid index occurred without reaching the programmed alert threshold. Conclusion A device-based algorithm that alerts patients in case of decreasing intrathoracic impedance facilitates the detection of HF deterioration. Future randomized, controlled trials are needed to test whether the tailored use of intrathoracic impedance monitoring can improve the ambulatory management of patients with chronic HF and an implanted device.